AGRICULTRAL SOLAR SPRAYER WITH MULTI APPLICATIONS - Venkateswarlu, M.; Kumar, Dr.M. Ashok; Nagakiran, M.; Nagakiran, M.; SagaKumar, K. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
A Solar Operated Pesticide Sprayer is a pump running on electricity generated by photovoltaic panels or thethermal energy available from collected sunlight as opposed to grid electricity or diesel run water pumps. Theoperation of solar powered pumps is more economical mainly due to the lower operation and maintenance costsand has less environmental impact than pumps powered by an internal combustion engine (ICE). Solar pumps areuseful where grid electricity is unavailable and alternative sources (in particular wind) do not provide sufficientenergy. The solar panels make up most (up to 80%) of the systems cost. The size of the PV-system is directlydependent on the size of the pump, the amount of water that is required (m³/d) and the solarIrradiance vailable. The solar sprayer has many advantages. Besides reducing the Cost of spraying, there is a saving on fuel/petrol. Also, the transportation cost for buying petrol is saved. The solar sprayer maintenance is simple. There is less vibration as compared to the petrol sprayer. The farmer can do the spraying operation by himself without engaging labour,thus increasing spraying efficiency